Advances in VNS efficiency and mechanisms of action on cognitive functions - Wang, Wendi; Li, Rui; Li, Chuangtao; Liang, Qimin; Gao, Xiaolin (Frontiers in Physiology, 2024)
Objective: This systematic review aims to comprehensively analyze the efficacy and underlying mechanisms of vagus nerve stimulation (VNS) in enhancing cognitive functions and its therapeutic potential for various cognitive impairments. The review focuses on the impact of VNS on emotional processing, executive functions, learning, memory, and its clinical applications in conditions such as epilepsy, depression, Alzheimer's disease, and other neurological disorders. Methods: A systematic search of electronic databases (PubMed, Scopus, Web of Science) was conducted using the keywords "vagus nerve stimulation," "cognitive enhancement," "emotional processing," "executive function," "learning and memory," "epilepsy," "depression," "Alzheimer's disease," "neurological disorders," "attention-deficit/hyperactivity disorder," "sleep disorders," and "long COVID." The inclusion criteria encompassed controlled trials, longitudinal studies, and meta-analyses published in English between 2000 and July 2024. Results: A comprehensive review of 100 articles highlighted the cognitive effects of Vagus Nerve Stimulation (VNS). Studies show that VNS, especially through transcutaneous auricular VNS (taVNS), enhances emotional recognition, particularly for facial expressions, and improves selective attention under high cognitive demands. Additionally, VNS enhances learning and memory, including associative memory and spatial working memory tasks. In clinical applications, VNS exhibits promising benefits for improving cognitive functions in treatment-resistant epilepsy, depression, and Alzheimer's disease. Conclusion: VNS represents a promising therapeutic approach for enhancing cognitive function across diverse patient populations. The reviewed evidence highlights its efficacy in modulating cognitive domains in healthy individuals and improving cognition in neurological conditions. However, the comparative effectiveness of different VNS modalities and the differential effects of online versus offline VNS on cognitive psychology require further investigation. Future research should focus on optimizing VNS protocols and elucidating specific cognitive domains that benefit most from VNS interventions. This ongoing exploration is essential for maximizing the therapeutic potential of VNS in clinical practice.